Sensing a revolution. Issue 4 (26th April 2016) - Steinmetz, Lars M; Jones, Allan
Abstract : New fully integrated biosensors that monitor molecular and physiological parameters throughout our bodies are set to revolutionize medicine and personalized healthcare. Abstract : New fully integrated biosensors that monitor molecular and physiological parameters throughout our bodies are set to revolutionize medicine and personalized healthcare.